(untitled) (Gadau Journal of Pure and Allied Sciences, 2023)
Diabetes mellitus is one of the most common metabolic disorders that is associated with many complications such as dyslipidemia and cardiovascular disease. This study aimed to evaluate the effects of alpha lipoic acid (ALA) on blood glucose levels and lipid profile in type-2 diabetic male Wistar rats. Thirty (30) Wistar rats weighing between 200 – 250 grams were distributed into six groups of five each (n=5). Diabetes was induced using a high-fat diet for eight weeks with a single low dose of streptozotocin (40 mg/kg) intraperitoneally at the end of the sixth week. Group I served as normoglycemic control and received 1 ml/kg normal saline; groups II, III, IV, V, and VI were diabetic and received 1 ml/kg normal saline; glibenclamide 1 mg/kg; ALA 100 mg/kg, ALA 200 mg/kg and ALA 400 mg/kg; respectively. All administrations were done orally for a duration of 21 days. Blood glucose level was determined using the glucose oxidase method. Serum was collected for lipid profile determination. The results obtained from this study showed that ALA across all doses (100 mg/kg, 200 mg/kg, and 400 mg/kg) decreased significantly (p < 0.05) the fasting blood glucose level (10.02 ± 0.71 mmol/L, 8.78 ± 0.94 mmol/L and 8.6 ± 0.68 mmol/L, respectively) when compared to the diabetic control group (20.06 ± 0.70 mmol/L). Lipid profiles were improved with HDL- and LDL- cholesterols increasing and decreasing significantly (42.60 ± 1.66 mg/dL and 1.12 ± 3.68 mg/dL) in the 400 mg/kg ALA group compared to the diabetic untreated group (37.00 ± 2.55 mg/dL and 26.31 ± 2.95 mg/dL, respectively). Therefore, the study demonstrated that ALA has both antihyperglycemic and antilipidemic in type-2 diabetic Wistar rats.